PENGARUH CUKA SALAK TERHADAP PENURUNAN GLUKOSA DARAH DAN HISTOPATOLOGI PANKREAS TIKUS DIABETES - Hamidatun, Hamidatun; Mandasari, Oty Kiki; Rosdiana, Indri; Widiyana, Septina Dwi (Program Kreativitas Mahasiswa - Penelitian, 2014)
Diabetes mellitus is indicated by elevated levels of blood glucose and progressive changes of the structure of pancreatic islet histopathology. Salacca vinegar made from suwaru salacca is one of alternative medicine of diabetes because contain acetate acid and antioxidant. The aim of this study is to investigate the effects of salacca vinegar on blood glucose and histopathologycal of pancreas of diabetic rats. This research is based on Pre and Post Test with Control Group Design. Ratus norvegicus rats were divided into 4 groups. There were normal group, diabetes, diabetes + salacca vinegar 0,4mL and diabetes + salacca vinegar 0,7mL. The results indicated that salacca vinegar had a significant blood glucose lowering effect diabetic rats. Group of diabetes + salacca vinegar 0,4mL reduced glucose concentration of 35,06%, diabetes + salacca vinegar 0,7mL of 32,50%. Based on histopathologycal of pancreas showed that salacca vinegar recover pancreatic beta cells damaged. Conclusion is salacca vinegar had a significant blood glucose lowering effect and recover pancreatic beta cells damaged.Â Keywords:Â  Blood glucose, Diabetes Mellitus, Pancreas Histopathology, Salacca Vinegar